2022
DOI: 10.1002/jper.21-0723
|View full text |Cite
|
Sign up to set email alerts
|

Is the degree of physiological bone remodeling a predictive factor for peri‐implantitis?

Abstract: Background The amount of initial physiological bone remodeling (IPBR) after implant placement varies and the ways it may play a role in peri‐implantitis development remains unknown. The aim of this retrospective study was to investigate the association between the amount of IPBR during the first year of implant placement and incidence of peri‐implantitis as well as the pattern of progressive bone loss. Methods Clinical and radiographic documentation of implants at the time of implant placement (T0), 1 year ± 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The results of our previous analysis [ 11 ], performed on the same sample at a follow-up of 2 years, showed that implants with increased MBL rates at 6 months after loading were likely to exhibit additional MBL. This correlation was confirmed by the present analysis, performed after 5 years of loading, which showed no statistically significant relationship between MBL progression and the onset of P. Similar results have been reported by Rodriguez et al [ 10 ], who evaluated in a sample of 45 patients receiving 57 implants the possible relationship between the amount of early MBL and the presence of P after 1 year of loading. These data indicated that, although most of the implants presenting a high initial level of MBL exhibited progressively high MBL in the following years, the degree of MBL progression did not influence the onset of P. Some authors [ 8 , 9 , 10 , 11 ] have speculated that if MBL during the healing/remodeling phase exceeds a certain threshold, it may create a niche for pathogenic microorganisms, providing a more anaerobic environment and promoting P. Therefore, the MBL level could already be indicative and predictive of the development of P during the remodeling phase.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of our previous analysis [ 11 ], performed on the same sample at a follow-up of 2 years, showed that implants with increased MBL rates at 6 months after loading were likely to exhibit additional MBL. This correlation was confirmed by the present analysis, performed after 5 years of loading, which showed no statistically significant relationship between MBL progression and the onset of P. Similar results have been reported by Rodriguez et al [ 10 ], who evaluated in a sample of 45 patients receiving 57 implants the possible relationship between the amount of early MBL and the presence of P after 1 year of loading. These data indicated that, although most of the implants presenting a high initial level of MBL exhibited progressively high MBL in the following years, the degree of MBL progression did not influence the onset of P. Some authors [ 8 , 9 , 10 , 11 ] have speculated that if MBL during the healing/remodeling phase exceeds a certain threshold, it may create a niche for pathogenic microorganisms, providing a more anaerobic environment and promoting P. Therefore, the MBL level could already be indicative and predictive of the development of P during the remodeling phase.…”
Section: Discussionsupporting
confidence: 93%
“…It has been also hypothesized that a high degree of early marginal bone loss (MBL) might be a predictive factor for the subsequent onset of peri-implant inflammatory diseases [ 8 , 9 , 10 , 11 ]. Defining as “pathological” any MBL that exceeds the bone loss threshold during the healing/remodeling phase, several authors have highlighted that early increased MBL may be indicative of P development, as it may create a niche for pathogenic micro-organisms, providing a more anaerobic environment and promoting progressive bone loss [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusion criterium was diagnosis of peri-implantitis on at least one dental implant based on the definition from the consensus report of workgroup 4 of the 2017 World Workshop [ 32 ]. Because baseline data were available peri-implantitis diagnosis was based on (I) progressive bone loss beyond initial bone remodeling (CBL loss ≥ 2 mm), (II) increased PD compared with previous examinations in at least one site around the implant (PD ≥ 4 mm), and (III) presence of bleeding and/or suppuration on gentle probing [ 33 ] Initial full mouth or experimental site-specific dental plaque scores were not an inclusion criterium. Staging of periodontitis of the included patients was performed according to the 2017 classification [ 34 ].…”
Section: Methodsmentioning
confidence: 99%